High-Performance Anticorrosive Polyester Coatings on Mild Steel in Mixed Acid Mixtures Environments. (19th December 2019) - Ahmad, Bashir; Ahmad, Nasir M.; Yasir, Muhammad; Khan, Zulfiqar A.; Rafiq, Sikander
Abstract : Mild steel sample was selected from acid storage tanks used in industry as a substrate, and two advanced technological polymeric resin-based coatings were developed, designated as LAM-P resin based which is LAM-P/FR coating and LAM-V resin based which is LAM-V/FR coating. These coatings were applied over steel samples by using the hand lay-up process. FTIR test was conducted to confirm complete curing, and SEM analyses were used to investigate surface morphology. A series of electrochemical tests were performed in acidic environment (mixed acid solution 56% H2 SO4 + 26% HNO3 + 18% H2 O by weight). The results indicated successful development of LAM-P/FR and LAM-V/FR to obtain coatings with desirable characteristics such as anticorrosion, thickness, adhesion, stability, charge store and more resistance to acidic environments. EIS data for mixed acid storage media demonstrated that LAM-V/FR coating has higher strength in mixed acid solution, higher values of impedance and phase shift, higher value of R pore, and low value of C c ; corrosion rate percentage reduction is 96% of LAM-P/FR and 99.96% of LAM-V/FR compared to bare mild steel sample. The outcomes of this study can lead to assist in design guidelines for anticorrosive coating for industrial applications.